A census of actin-associated proteins in humans - Meenakshi S, Iyer; Rao, Madan; Mayor, Satyajit; Sowdhamini, Ramanathan (Frontiers in Cell and Developmental Biology, 2023)
Actin filaments help in maintaining cell structure and coordinating cellular movements and cargo transport within the cell. Actin participates in interaction with several proteins and also with itself to form the helical filamentous actin (F-actin). Actin-binding proteins (ABPs) and actin-associated proteins (AAPs) coordinate actin filament assembly and processing, regulate the flux between globular G-actin and F-actin in the cell and help maintain cellular structure and integrity. We have used protein-protein interaction data available through multiple sources (STRING, BioGrid, MENTHA and a few others), functional annotation and classical actin-binding domains to identify actin-binding and actin-associated proteins in the human proteome. Here, we report 2482 AAPs and present an analysis of their structural and sequence domains, functions, evolutionary conservation, cellular localisation, abundance and tissue-specific expression patterns. This analysis provides a base for the characterisation of proteins involved in actin dynamics and turnover in the cell.